Analytical model for calibrating laser intensity in strong-field-ionization experiments - Zhao, Song-Feng; Le, Anh-Thu; Jin, Cheng; Wang, Xu; Lin, C. D. (My University, 2016)
The interaction of an intense laser pulse with atoms and molecules depends extremely nonlinearly on the laser intensity. Yet experimentally there still exists no simple reliable methods for determining the peak laser intensity within the focused volume. Here we present a simple method, based on an improved Perelomov-Popov-Terent'ev model, that would allow the calibration of laser intensities from the measured ionization signals of atoms or molecules. The model is first examined by comparing ionization probabilities (or signals) of atoms and several simple diatomic molecules with those from solving the time-dependent Schrödinger equation. We then show the possibility of using this method to calibrate laser intensities for atoms, diatomic molecules as well as large polyatomic molecules, for laser intensities from the multiphoton ionization to tunneling ionization regimes.